2004
DOI: 10.1073/pnas.0404852102
|View full text |Cite
|
Sign up to set email alerts
|

CD98hc (SLC3A2) mediates integrin signaling

Abstract: Integrins regulate cellular behaviors through signaling pathways, including Rho GTPases and kinases. CD98 heterodimers, comprised of a heavy chain (CD98hc, SLC3A2) and one of several light chains, interact with integrins through CD98hc. CD98hc overexpression leads to anchorage-independent cell growth and tumorigenesis in 3T3 fibroblasts and activates certain integrin-regulated signaling pathways. To establish the biological function of CD98hc, we disrupted the gene and analyzed CD98hc-null cells. Here we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
267
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(277 citation statements)
references
References 33 publications
8
267
1
1
Order By: Relevance
“…In addition to its role in amino acid transport, CD98hc interacts with integrins and regulates their signaling properties (Fenczik et al, 1997(Fenczik et al, , 2001Chandrasekaran et al, 1999;Zent et al, 2000;Kolesnikova et al, 2001;Merlin et al, 2001;Feral et al, 2005). Our studies and those of others have been instrumental in understanding how CD98hc physically and functionally interacts with integrins and regulates their functions in vitro (Merlin et al, 2001;Rintoul et al, 2002;Henderson et al, 2004;Feral et al, 2005Feral et al, , 2007. Knockdown studies in human keratinocytes in vitro concluded the importance of CD98hc for cell adhesion and differentiation by regulating 1 integrin trafficking (Lemaître et al, 2011).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…In addition to its role in amino acid transport, CD98hc interacts with integrins and regulates their signaling properties (Fenczik et al, 1997(Fenczik et al, , 2001Chandrasekaran et al, 1999;Zent et al, 2000;Kolesnikova et al, 2001;Merlin et al, 2001;Feral et al, 2005). Our studies and those of others have been instrumental in understanding how CD98hc physically and functionally interacts with integrins and regulates their functions in vitro (Merlin et al, 2001;Rintoul et al, 2002;Henderson et al, 2004;Feral et al, 2005Feral et al, , 2007. Knockdown studies in human keratinocytes in vitro concluded the importance of CD98hc for cell adhesion and differentiation by regulating 1 integrin trafficking (Lemaître et al, 2011).…”
mentioning
confidence: 65%
“…CD98hc deletion in vitro impairs integrin-dependent functions, in particular as a result of a FAK phosphorylation defect (Feral et al, 2005(Feral et al, , 2007. We now show that CD98hc absence in the epidermis in vivo does not phenocopy adhesion Surprisingly, in 4OHT-treated K14-CreER T2 ; CD98hc fl/fl mice that displayed a major defect in wound healing, RhoA activity was persistently higher from days 3 to 7 after wounding, with no apparent regulation (Fig.…”
Section: Cd98hc-deficient Epidermis Displays a Strong In Vivo C-src Amentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Expression of the transmembrane glycoprotein CD98, encoded by SLC3A2, is increased in various carcinomas. [4][5][6][7] Recently, we generated both gain-and loss-of-function mouse models featuring genetic manipulation of CD98 expression specifically in intestinal epithelial cells (IECs), and explored the roles of CD98 in intestinal homeostasis, inflammation, and colitis-associated tumorigenesis.…”
mentioning
confidence: 99%
“…It is well documented from the work of others that 4F2 interacts with integrins and affects integrin pathways, altering the activation state of Akt and RacGTPase, leading to changes in cellular morphology, susceptibility to apoptosis and contributing to tumorigenesis. 29 The examination of these pathways and their potential link to exogenous LAT1 expression will be of interest.…”
Section: Discussionmentioning
confidence: 99%